High-performance regenerated ternary material and preparation method thereof
By performing high carbonation and prelithiation of waste ternary positive electrode materials on the surface and sintered with flux, the problem of not obvious improvement in the performance of regenerated ternary positive electrode materials is solved, and the discharge capacity of the material is significantly improved and The effect of capacity retention.
Patent Information
- Application Number
- CN202411571834.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
In the prior art, the performance improvement of the regenerated ternary cathode material is not obvious, and the preparation method needs to be improved to improve the discharge capacity and capacity retention rate of the material.
By pretreating the waste ternary positive electrode active material to form a ternary positive electrode powder with a surface that is highly carbonated, and combining prelithiation and flux coating technology, high-performance regenerated ternary material is prepared. The specific steps include stirring the used ternary positive electrode active material in supersaturated carbon dioxide aqueous solution and air-drying to form a ternary positive electrode powder with high carbonation on the surface; then mixing the lithium source and long-chain carbon alcohol to form starch-based lithium, and high carbonic acid on the surface. The ternary positive electrode powder is mixed to form the prelithalized ternary positive electrode powder; finally mixed with the flux to sinter.
This method greatly improves the performance of waste ternary recycled materials, significantly improves its discharge capacity and capacity retention rate, and has low process cost and reduced energy consumption, which is universal and efficient.
Smart Images

Figure CN119430314A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ternary materials, and in particular to a high-performance recycled ternary material and a preparation method thereof. Background Art
[0002] my country is a major battery producer and consumer. Civilian batteries are the most widely used type of battery. The amount of discarded batteries is also very large every year. The discarded batteries pose a serious threat to environmental safety and also cause a waste of resources. Therefore, it is necessary to recycle the waste batteries. For example, after the waste ternary lithium battery is safely discharged, it is disassembled and shelled under a protective gas atmosphere to obtain the ternary positive electrode active material, and then soaked in potassium hydroxide solution, and then washed with deionized water to obtain the positive electrode active material with the electrolyte component removed; the treated ternary positive electrode active material is placed in a supercritical extraction device to obtain the extraction product of the ternary positive electrode material. However, the performance of the extraction product of the ternary positive electrode material is not significantly improved, and it is still necessary to improve the preparation method of the regenerated ternary positive electrode material to improve the performance of the regenerated ternary positive electrode material.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a high-performance recycled ternary material and a preparation method thereof. The preparation method provided in the embodiment of the present invention can greatly improve the performance of the waste ternary recycled material and increase its discharge capacity and capacity retention rate.
[0005] The implementation method of the present invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing a high-performance recycled ternary material, comprising:
[0007] Pre-treating the waste ternary positive electrode active material to form a ternary positive electrode powder with high surface carbonation;
[0008] Mixing a lithium source and a long-chain carbon alcohol to form starch-based lithium; mixing the starch-based lithium with the surface highly carbonated ternary positive electrode powder to form a pre-lithiated ternary positive electrode powder, wherein the long-chain carbon alcohol is selected from alcohols with a carbon number greater than 5;
[0009] The pre-lithiated ternary cathode powder and flux are mixed and sintered.
[0010] In an optional embodiment, the long-chain carbon alcohol is a monohydric alcohol; more preferably a monohydric terminal hydroxyl alcohol;
[0011] Preferably, the structural formula of the long-chain carbon alcohol is as follows: 1-C n H (2n+1) OH, wherein n≥5; most preferably n-octanol.
[0012] In an optional embodiment, the lithium source is selected from lithium hydroxide.
[0013] In an optional embodiment, 1-5 g of lithium source corresponds to 100 ml of the long-chain carbon alcohol.
[0014] In an optional embodiment, the method comprises: mixing and stirring the starch-based lithium with the surface highly carbonated ternary cathode powder, and then filtering and drying to form the pre-lithiated ternary cathode powder.
[0015] In an optional embodiment, the flux is selected from one or more combinations of lithium niobate, lithium phosphate, strontium nitrate, strontium oxide, strontium hydroxide, and barium nitrate, and lithium niobate is most preferred.
[0016] In an optional embodiment, the amount of the flux used is 500-5000 ppm.
[0017] In an optional embodiment, sintering includes negative pressure high temperature sintering;
[0018] Preferably, the sintering conditions include: pressure of -100 MPa to -300 MPa, temperature of 700-900° C., and time of 2-6 h.
[0019] In an optional embodiment, the pretreatment includes: stirring the waste ternary positive electrode active material in a supersaturated carbon dioxide aqueous solution and then air-drying;
[0020] Preferably, the pretreatment is supercritical extraction;
[0021] Preferably, the extraction pressure is 15-30 MPa; the extraction temperature is 30-60° C.; the extraction time is 1-2 h; and the extraction gas is carbon dioxide.
[0022] In a second aspect, the present invention provides a high-performance recycled ternary material, which is prepared by the method for preparing a high-performance recycled ternary material described in any one of the aforementioned embodiments.
[0023] The present invention has the following beneficial effects: the embodiment of the present invention utilizes pre-treatment to form carbonation on the surface of the ternary positive electrode material, combined with subsequent pre-lithiation and flux coating technology, to achieve a synergistic effect, greatly improving the performance of waste ternary recycled materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0025] Figure 1 A schematic diagram of the principle of the method for preparing the high-performance recycled ternary material provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] The present invention provides a method for preparing a high-performance regenerative ternary material, and a preparation principle diagram. Figure 1 , the specific preparation process is as follows:
[0028] S1, pre-treatment;
[0029] The waste ternary positive electrode active material peeled off from the electrode sheet is pre-treated to obtain the ternary positive electrode powder with high surface carbonation.
[0030] The method of stripping the waste ternary positive electrode active material from the waste electrode sheet can refer to the steps or methods in the prior art, and the embodiments of the present invention will not be described in detail.
[0031] Specifically, the pretreatment includes: stirring the waste ternary positive electrode active material in a supersaturated carbon dioxide aqueous solution and then air-drying; using the supersaturated carbon dioxide aqueous solution for pretreatment can not only remove impurities from the waste ternary material powder, but also remove the residual F - (electrolyte), Al element (aluminum foil). At the same time, the supersaturated carbon dioxide bubbles can form a dense lithium carbonate layer on the surface of the ternary positive electrode material, which is beneficial to subsequent operations and improve the performance of the ternary positive electrode material.
[0032] Specifically, the embodiment of the present invention adopts supercritical extraction to achieve pretreatment. Supercritical extraction is only an example of the embodiment of the present invention. Other methods can also be used as long as the waste ternary positive electrode active material is stirred in a supersaturated carbon dioxide aqueous solution.
[0033] Specifically, the extraction pressure is 15-30Mpa; the extraction temperature is 30-60°C; the extraction time is 1-2h; and the extraction gas is carbon dioxide.
[0034] S2, forming a pre-lithiated ternary cathode powder;
[0035] A lithium source and a long-chain carbon alcohol are mixed to form starch-based lithium, and the starch-based lithium is mixed with the surface highly carbonated ternary positive electrode powder to form a pre-lithiated ternary positive electrode powder.
[0036] The starch-based lithium formed can be adsorbed on the surface of waste ternary materials through the van der Waals force between the lithium carbonate layer and the starch base. Compared with directly adding the lithium source, this process has a higher utilization rate of the lithium source, shortens the diffusion path of lithium entering the surface and interior of the material, and reduces the reaction time between the lithium source and the material during sintering.
[0037] Specifically, the lithium source and the long-chain carbon alcohol are mixed and dissolved to form a starch-based lithium solution, which is then mixed with the surface highly carbonated ternary cathode powder and stirred at room temperature for 2-4 hours, followed by suction filtration and drying to obtain the pre-lithiated ternary cathode powder.
[0038] Among them, the long-chain carbon alcohol is selected from alcohols with a carbon number greater than 5; if the carbon number of the long-chain carbon alcohol is too low, for example, the long-chain carbon alcohol is selected from methanol, ethanol and butanol, etc., it is impossible to form a starch-like long-chain group, and it is even more impossible to effectively form van der Waals forces to adhere to the surface of the ternary material matrix, and cooperate with the subsequent flux, and then it is impossible to effectively improve the performance of the regenerated ternary material.
[0039] Specifically, the long-chain carbon alcohol is a monohydric alcohol; more preferably a monohydric terminal hydroxyl alcohol; for example, 1-C n H (2n+1) OH, wherein n≥5; preferably 5≤n≤10, for example including but not limited to n-octanol. The lithium source is selected from lithium hydroxide. 1-5g of the lithium source corresponds to 100ml of the long-chain carbon alcohol. The above conditions are conducive to the formation of van der Waals forces, which in turn is conducive to improving the performance of the regenerated ternary material.
[0040] S3, sintering;
[0041] The pre-lithiated ternary cathode powder and flux are mixed and sintered. Specifically, the pre-lithiated ternary cathode powder and flux are dry mixed, and then sintered at a negative pressure and high temperature, and the desired regenerated ternary material is obtained after cooling.
[0042] The embodiment of the present invention performs flux-coated high-temperature sintering after pre-lithiation. Under the effect of pre-lithiation, the sintering time is shorter, and the energy consumption in industry is significantly reduced. In addition, low-cost additives and processes are used in the process, which is green, environmentally friendly and universal.
[0043] The amount of flux used is 500-5000 ppm, for example, 500 ppm, 1000 ppm, 2000 ppm, 3000 ppm, 4000 ppm, 5000 ppm, or any value between 500-5000 ppm.
[0044] The flux is selected from one or more combinations of lithium niobate, lithium phosphate, strontium nitrate, strontium oxide, strontium hydroxide, and barium nitrate, and lithium niobate is most preferred.
[0045] Specifically, the sintering conditions include: pressure of -100Mpa to -300Mpa, temperature of 700-900°C, and time of 2-6h.
[0046] In a second aspect, the present invention provides a high-performance recycled ternary material, which is prepared by the method for preparing a high-performance recycled ternary material described in any one of the aforementioned embodiments.
[0047] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0048] Example 1
[0049] The embodiment of the present invention provides a method for preparing a high-performance recycled ternary material, comprising:
[0050] S1: The waste ternary positive electrode active material peeled off from the electrode piece is placed in a supercritical extraction device, and the extraction pressure is set to 20Mpa, the extraction temperature is 50°C and the extraction time is 1h, so as to obtain a ternary positive electrode powder with high surface carbonation;
[0051] S2: dissolving lithium hydroxide monohydrate in n-octanol at a ratio of 1 g / 100 mL to prepare a starch-based lithium solution; then performing an ICP test on the ternary powder obtained in S1 to obtain the Li / (Ni+Co+Mn) value of the waste ternary powder, adding the ternary powder obtained in S1 to the solution based on the weight of the additional lithium supplement required for this design value of 1.05, stirring at room temperature for 4 hours, filtering, and vacuum drying at 75°C to obtain a pre-lithiated ternary positive electrode powder;
[0052] S3: The powder obtained in S2 was mixed with 2000ppm lithium niobate in a high-speed mixer at 800r / min for 10min, sintered at 800°C for 4h at -150Mpa, and the regenerated ternary material was obtained after cooling.
[0053] Example 2-3
[0054] Embodiment 2-3 of the present invention provides a method for preparing a high-performance recycled ternary material. The operation of the preparation method is basically the same as that of the preparation method provided in Embodiment 1, except that some conditions are different.
[0055] Example 2: The long-chain carbon alcohol is n-pentanol, 2 g of lithium hydroxide corresponds to 100 ml of n-pentanol; the flux is lithium phosphate, and the amount of lithium phosphate used is 3500 ppm.
[0056] Example 3: The long-chain carbon alcohol is n-heptanol, 5 g of lithium hydroxide corresponds to 100 ml of n-pentanol; the flux is strontium hydroxide, and the amount of strontium hydroxide used is 1500 ppm.
[0057] Comparative Example 1: The positive electrode material provided in this comparative example is the waste ternary positive electrode active material peeled off from the electrode sheet prepared in Example 1.
[0058] Comparative Example 2: The preparation method of the positive electrode material provided in this comparative example is as follows:
[0059] The waste ternary positive electrode active material peeled off from the electrode piece is subjected to ICP testing to obtain the Li / (Ni+Co+Mn) value of the waste ternary powder. After being mixed with the additional lithium hydroxide required for the design value of 1.05, it is sintered at low pressure and high temperature to form a ternary positive electrode material. The sintering conditions include: -150Mpa, 800℃ and 10h.
[0060] Comparative Example 3: The preparation method of the positive electrode material provided in this comparative example is as follows:
[0061] The waste ternary positive electrode active material peeled off from the electrode sheet and 2000ppm lithium niobate were stirred in a high-speed mixer at 800r / min for 10min, sintered at 800℃ for 4h at -150Mpa, and then cooled to obtain the regenerated ternary material.
[0062] Comparative Example 4: The preparation method of the positive electrode material provided in this comparative example is as follows:
[0063] The pre-lithiated ternary positive electrode powder prepared in Example 1 was sintered at 800° C. for 4 h at -150 MPa, and then cooled to obtain the regenerated ternary material, that is, no flux was added.
[0064] Comparative Example 5: The preparation method of the positive electrode material provided in this comparative example is as follows:
[0065] Lithium hydroxide monohydrate was dissolved in ethanol at a ratio of 1 g / 100 mL to prepare an ethanol solution of lithium hydroxide; then the surface highly carbonated ternary cathode powder of S1 of Example 1 was added to obtain a pre-lithiated ternary cathode powder; and the conditions and steps of S3 of Example 1 were used to form a regenerated ternary material.
[0066] Experimental example
[0067] The ternary positive electrode materials of Examples 1-2 and Comparative Examples 1-5 were tested to measure their discharge capacity (4.45 V, 0.5 C, mAh / g) and 100-cycle capacity retention rate (%).
[0068] The detection method is as follows: the obtained recycled ternary material, carbon black, and polytetrafluoroethylene (PVDF) are mixed uniformly at a mass ratio of 94:3:3, and N-methyl-2-pyrrolidone (NMP) is added and ground into a uniform slurry, which is then coated on aluminum foil and placed in a vacuum drying oven at 120°C for 12 hours to make a button battery positive electrode, and a metal lithium sheet is used as the negative electrode and 1M lithium hexafluorophosphate is used as the electrolyte to make a CR2025 button battery. The first cycle discharge gram capacity of the button battery at a rate of 0.5C and the capacity retention rate of 100 cycles at 45°C can be exported by the LANDdt test software. The results are shown in Table 1.
[0069] Table 1 Test results
[0070]
[0071]
[0072] According to the above Table 1, the discharge capacity of the waste ternary material powder in Comparative Example 1 is low and the cycle performance is poor; in Comparative Example 2, after conventional long-term high-temperature lithium supplementation sintering, its electrical performance can only be slightly improved, and its performance cannot be effectively improved; in Comparative Examples 3-4, the steps of the present invention are disassembled, and although Comparative Example 4 can greatly improve the electrical performance compared with the other comparative examples, it is far less than the effect of Examples 1-3; and Comparative Example 5 in the present invention changes S2 to use low-carbon chain alcohol (ethanol), and the improvement effect is poor. After comparing the above data, it can be seen that the steps described in the present invention have an effective synergistic effect on the electrical performance improvement of waste ternary material powder, can greatly improve the electrical performance of the reused waste ternary material, and use low raw material costs, high-temperature sintering time is short, and has universality and high efficiency.
[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-performance recycled ternary material, characterized in that: include: Pre-treating the waste ternary positive electrode active material to form a ternary positive electrode powder with high surface carbonation; Mixing a lithium source and a long-chain carbon alcohol to form starch-based lithium; mixing the starch-based lithium with the surface highly carbonated ternary positive electrode powder to form a pre-lithiated ternary positive electrode powder, wherein the long-chain carbon alcohol is selected from alcohols with a carbon number greater than 5; The pre-lithiated ternary cathode powder and flux are mixed and sintered.
2. The method for preparing high-performance recycled ternary materials according to claim 1, characterized in that: The long-chain carbon alcohol is a monohydric alcohol; more preferably a monohydric terminal hydroxyl alcohol; Preferably, the structural formula of the long-chain carbon alcohol is as follows: 1-C n H (2n+1) OH, wherein n≥5; n-octanol is most preferred.
3. The method for preparing high-performance recycled ternary materials according to claim 1, characterized in that: The lithium source is selected from lithium hydroxide.
4. The method for preparing high-performance recycled ternary materials according to claim 1, characterized in that: 1-5g of lithium source corresponds to 100ml of the long-chain carbon alcohol.
5. The method for preparing a high-performance recycled ternary material according to any one of claims 1 to 4, characterized in that: include: The starch-based lithium and the surface highly carbonated ternary cathode powder are mixed and stirred, and then filtered and dried to form the pre-lithiated ternary cathode powder.
6. The method for preparing high-performance recycled ternary materials according to claim 1, characterized in that: The flux is selected from one or more combinations of lithium niobate, lithium phosphate, strontium nitrate, strontium oxide, strontium hydroxide, and barium nitrate, and lithium niobate is most preferred.
7. The method for preparing a high-performance recycled ternary material according to claim 1 or 6, characterized in that: The dosage of the flux is 500-5000ppm.
8. The method for preparing a high-performance recycled ternary material according to claim 1 or 6, characterized in that: Sintering includes negative pressure high temperature sintering; Preferably, the sintering conditions include: pressure of -100 MPa to -300 MPa, temperature of 700-900° C., and time of 2-6 h.
9. The method for preparing high-performance recycled ternary materials according to claim 1, characterized in that: The pretreatment comprises: stirring the waste ternary positive electrode active material in a supersaturated carbon dioxide aqueous solution and then air-drying; Preferably, the pretreatment is supercritical extraction; Preferably, the extraction pressure is 15-30 MPa; the extraction temperature is 30-60° C.; the extraction time is 1-2 h; and the extraction gas is carbon dioxide.
10. A high-performance recycled ternary material, characterized in that: The high-performance recycled ternary material is prepared by the preparation method of the high-performance recycled ternary material described in any one of claims 1 to 9.
Citation Information
Patent Citations
Method for recycling waste lithium cobalt oxide battery through multi-component composite supercritical carbon dioxide system
CN114583314A
Direct regeneration method for positive electrode material of waste lithium ion battery
CN114976334A
High-specific-energy aqueous lithium ion battery and preparation method thereof
CN115275208A
Method of treating lithium battery to recycle its materials
EP1009058A1
A recycling method for the spent lithium ion secondary battery using carbon dioxide
KR102132120B1